'I can sit and talk to her': Aboriginal people, chronic low back pain and healthcare practitioner communication - Lin, I.; O'Sullivan, Peter; Coffin, J.; Mak, Donna; Toussaint, S.; Straker, Leon (The Royal Australian College of General Practitioners, 2014)
BACKGROUND: Chronic low back pain (CLBP) is a complex issue to manage in primary care and under-researched in Aboriginal populations. Good communication between practitioners and patients is essential but difficult to achieve. This study examined communication from the perspective of Aboriginal people with CLBP in regional and remote Western Australia. METHODS: Qualitative, in-depth interviews were conducted with 32 adults with CLBP who identify as Aboriginal. The approach and analysis were informed by clinical ethnography and cultural security. RESULTS: Barriers to communication related to communication content, information that was not evidence-based, miscommunications, communicative absence and the use of medical jargon. Enablers related to communication style described as ‘yarning’, a two-way dialogue, and healthcare practitioners with good listening and conversational skills. DISCUSSION: Health practitioners need to consider communication content and style to improve interactions with Aboriginal people with CLBP. A ‘yarning’ style may be a useful framework. Findings may be pertinent to other populations.